Model Pengembangan Agrowisata Berbasis Kearifan Lokal (Studi Kasus di Desa Kebon Agung Kecamatan Imogiri Kabupaten Bantul DIY) - Sriyadi, Sriyadi (Universitas Muhammadiyah Yogyakarta, 2016)
The purpose of this study is to provide an explanation of agrotourism development model, based on local wisdom. In the first year, the study aims to determine the impact of agrotourism development on increasing value-added agricultural products, farmers' income level and distribution of farmers’ income. Research carried out by survey and interviews with farmers and stakeholders as well as field observation. The result shows that the development of agrotourism can encourage farmers to do the processing of agricultural products and improve farming management both on-farm and off-farm, which in turn can increase the income of farm households significantly. The study recommends to optimize the processing of agricultural products and improve farming management both on-farm and off-farm.